Direct Purification of Digestate Using Polymeric Ultrafiltration Membranes: Influence of Materials on Filtration Behavior and Fouling Characteristics - Caide Yue; Yongxing Chen; Wanqin Zhang; Yunhao Zheng; Xuzhao Hu; Bin Shang (Membranes, 2022)
In-depth exploration of filtration behavior and fouling characteristics of polymeric ultrafiltration (UF) membranes can provide guidance for the selection of materials and the control of membrane fouling during the purification of digestate. In this study, four types of polymeric membranes, (polyethersulfone (PES), polysulfone (PS), polyvinylidene fluoride (PVDF), and polyacrylonitrile (PAN)), were employed to filter digestate from swine manure. The results showed that the viscosity of the digestate dropped from 45.0 ± 11.3 mPa·s to 18.0 ± 9.8 mPa·s, with an increase in temperature from 30.0 °C to 45.0 °C. The four membrane fluxes all increased by more than 30%, with the cross flow velocity increasing from 1.0 m s−1 to 2.0 m s−1. During the batch experiments, the flux maintenance abilities of the membranes were in the order: PAN > PS > PVDF > PES. There were no significant differences in the effects of membrane materials on the removal of COD, TN, and TP (p < 0.05). For UV254 removal efficiency, PS showed the highest efficiency (68.6%), while PVDF showed the lowest efficiency (63.4%). The major fouling type was irreversible hydraulic fouling, and the main elements of scaling were C, O, S, and Ca. Pseudomonadales were the dominant bacteria in the PS (26.2%) and in the PVDF (51.4%) fouling layers, while Bacteroidales were the dominant bacteria in the PES (26.8%) and in the PAN (14.7%) fouling layers. The flux recovery rates (FRRs) of the cleaning methods can be arranged as follows: NaClO > NaOH > Citric acid ≈ Tap water. After NaClO cleaning, the PVDF membrance showed the highest FRR (73.1%), and the PAN membrane showed the lowest FRR (30.1%).